Vegetative status in patients with transient ischemic attack and stroke - Halinouskaya , N. V.; Samsonau , S. V. (Neurologijos seminarai, 2018)
Background. Presented work aims to study the status of the autonomic nervous system (ANS) in two groups of patients during 10-day acute period. One group consists of patients with transient ischemic attack (TIA) and another group consists of patients with stroke. The latter group includes patients with various size of stroke.Prospective cohort study was carried out in the Department of Neurology and Neurosurgery of the Gomel State Medical University, Stroke Unit of the Gomel Regional Veterans Hospital, between May 2014 and March 2016. The groups included in the study were composed as follows: TIA group contained 13 patients and Stroke group contained 84 patients, including 61 with size of stroke lower than 15 mm (lacunar stroke – LS) and 23 with size of stroke bigger than 15 mm (total stroke – TS). Heart rate variability (HRV) was used to describe status of the ANS. It was measured at the 1st and 10th day of staying in the hospital. Obtained HRV records were analyzed using the following four parameters: SDNN (standard deviation of the normal-to-normal R-R intervals, in ms), ΔX (the difference between maximal and minimal R-R interval, in ms), Mo (mode of the duration of R-R intervals, in ms), AMo (amplitude of the R-R intervals mode, in percent).Results. For the HRV taken on the 1st day of admission, the dependence between ΔX (representing activity of parasympathetic part of ANS) and Mo (representing sympathetic part of ANS) was found to be significantly different in TIA and TS groups (p=0.01).Conclusion. The key difference between TIA and TS is a difference in the relationship between the humoral regulation of the activities of the ANS and the parasympathetic part activity at the 1st day, which determines specific features of pathogenesis of the transient ischemia.
Keywords: transient ischemic attack; lacunar stroke; total stroke; sympathetic and parasympathetic parts of autonomic nervous system